The politics of well-being : towards a more ethical world - Clohesy, Anthony M. (Abingdon, Oxon ; New York, NY : Routlegde, 2021)
"The Politics of Well-Being argues that the relationship between well-being and ethical life has been overlooked. The more specific argument of the book is that ethical life requires political engagement, and the emergence of a society committed to critical thinking. It is argued that these conditions allow for our ordination and confirmation as ethical subjects. While well-being can be experienced in different ways, it is claimed that, after experience of ethical life, a more sustainable form of it is revealed to us, a form which we would be drawn to preserve, a form which can be constituted as an object of hope. While the book draws on philosophical themes, its main focus is political. This is because its primary objective is to identify and to examine what needs to be done in order to realise ethical life. Its main focus in this respect is the identification and examination of the barriers which need to be overcome if ethical life is to be realised. It is acknowledged that this will not be an easy task. Indeed, it may be an impossible task. However, despite these barriers, and despite the dark days we are living through, the book is a call to hope rather than a surrender to despair. This book will be of interest to students of politics, psychology, cultural studies, philosophy and sociology, as well as anyone else interested in exploring new ideas about how the make the world a better place"--
Introduction -- Well-being -- Optimism -- Populism -- Escapism -- Nihilism -- Hope -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Social ethics; Political ethics; Well-being -- Political aspects; Well-being -- Moral and ethical aspects; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / General; POLITICAL SCIENCE / Public Policy / Social Policy